A new species of Suwallia Ricker, 1943 from Japan, and the identity of Alloperla teleckojensis Šámal, 1939 (Plecoptera: Chloroperlidae) - Li, Wenliang; Wang, Yingying; Wang, Ying; Li, Weihai (Zootaxa, 2021)
A new species of the genus Suwallia from Japan, S. kawaii sp. n. is described, illustrated with color images and compared with related taxa. Based on the examination of the holotype, we consider Alloperla teleckojensis Šámal, 1939 is synonymized with Alloperla deminuta Zapekina-Dulkeit, 1970, and the former was a valid name. The name S. errata sp. n. is given for the widespread species hitherto known as Suwallia teleckojensis sensu Zapekina-Dulkeit (1955).